Seed Characteristics of Soybean Cultivars As Affected by Foliar Application of Elicitors - Hasanah, Y; Aziz Mahmud Siregar, L; Mawarni, L (KnE Life Sciences, 2019)
The objective of the research was to determine seed characteristics of soybean cultivars on the foliar application of elicitors. The research used a randomized block design with three factors and three replications. The first factor was soybean cultivars (Anjasmoro and Wilis). The second factor was the foliar application of elicitors consisted of without elicitor; chitosan (1 mg ⋅ mL−1), methyl jasmonate (0.5 mM) and salicylic acid (0.5 mM). The third factor was the time of foliar application of elicitors consisted of V4 and R3. The results suggest that the response of each cultivar to the treatment type and timing of elicitor application is different. In Anjasmoro cultivar, the elicitor treatment of salicylic acid at R3 tend to produce the highest number of the filled pod (58.88 pod), while in Wilis cultivar, the elicitor treatment of methyl jasmonate at V4 tend to produce the highest number of the filled pod (73.63 pod). The yield response of dry weight of 100 seeds was observed with the application of chitosan at the R3 stage. Keywords: Anjasmoro Cultivar, Elicitor, Foliar application, Soybean, Wilis cultivar.